2019
DOI: 10.1103/physrevapplied.12.044006
|View full text |Cite
|
Sign up to set email alerts
|

Damping of Standing Spin Waves in Bismuth-Substituted Yttrium Iron Garnet as Seen via the Time-Resolved Magneto-Optical Kerr Effect

Abstract: We investigate spin-wave resonance modes and their damping in insulating thin films of bismuthsubstituted yttrium iron garnet by performing femtosecond magneto-optical pump-probe experiments. For large magnetic fields in the range below the magnetization saturation, we find that the damping of high-order standing spin-wave (SSW) modes is about 40 times lower than that for the fundamental one. The observed phenomenon can be explained by considering different features of magnetic anisotropy and exchange fields t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…The frequencies of the low-frequency modes are in the range of SW frequencies in Bi-YIG films [43,44,57,58]. To clarify the nature of these modes, we investigated their frequencies as a function of the mode number.…”
Section: Results and Disccussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequencies of the low-frequency modes are in the range of SW frequencies in Bi-YIG films [43,44,57,58]. To clarify the nature of these modes, we investigated their frequencies as a function of the mode number.…”
Section: Results and Disccussionmentioning
confidence: 99%
“…On the other hand, for around 15 years, the excitation of SSWs with femtosecond laser pulses has been limited to conducting [9,41,42] and semiconducting [13,15,16] magnets. In our recent papers, we demonstrated that a femtosecond laser pulse can excite SSWs in insulating magnetic films of bismuth-substituted YIG with high in-plane magnetic anisotropy [43,44]. In this context, an important fundamental study is to investigate the possibility to take advantage of femtosecond laser pulses to trigger high-frequency SSWs in bismuth-substituted YIG films buried below a thick metallic structure.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the use of spin pumping as a driving force instead of optical excitations opens up tantalizing routes toward engineering ultrafast spintronic devices with the grand advantage of being highly scalable. This is in contrast to opto-magnetic studies [8][9][10][11][12][13], where a laser beam is used to excite ultrafast carrier or magnetic dynamics. For instance, in the recent proposal by Kampfrath et at [9], a femtosecond laser beam is used to generate nonequilibrium electron distributions in a geometry constituted of a thin ferromagnetic iron film combined with a thin noble metal layer.…”
mentioning
confidence: 99%
“…From a practical point of view, light polarization (helicity) can thus be used to control any ultrafast phenomena that are influenced by the lattice strain (or lattice heating). For example, in Bi-substituted iron garnets, it was recently demonstrated that an ultrafast heating of lattice can excite high frequency spin waves [20,66,67] and induce a full magnetization switching [68]. By choosing the appropriate pump wavelength to maximize the effect of MCD on lattice heating, it will be therefore possible to use the polarization of light in order to: (i) control the amplitude of the spin waves and (ii) obtain a helicity-dependent optical magnetization switching in magnetic insulators.…”
mentioning
confidence: 99%